2021
DOI: 10.25115/eea.v39i4.4479
|View full text |Cite
|
Sign up to set email alerts
|

Integrating resource-based view and performance improvement theory in developing maintenance management continuous improvement model: A conceptual framework

Abstract: The local authority in Malaysia is the giant holder of public assets and they are obligated in performing better management to ensure the assets are of prominent quality to serve the needs of the local people. The local authority should take initiatives in having the right systems in managing and maintaining their assets. Therefore, the purpose of this study is to explore the maintenance management practices and performance improvement techniques to be integrated into developing the continuous improvement mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This is due to these maintenance strategies were widely adopted in maintenance, research [50]. Therefore, scholars in maintenance management field concluded that the main maintenance practices in industrial sector can be divided into two, Preventive Maintenance (PM) and Corrective Maintenance (CM) [51].…”
Section: Maintenance Managementmentioning
confidence: 99%
“…This is due to these maintenance strategies were widely adopted in maintenance, research [50]. Therefore, scholars in maintenance management field concluded that the main maintenance practices in industrial sector can be divided into two, Preventive Maintenance (PM) and Corrective Maintenance (CM) [51].…”
Section: Maintenance Managementmentioning
confidence: 99%